PENGARUH PEMBELAJARAN BERBASIS STEM TERHADAP PEMAHAMAN KONSEP, KETERAMPILAN BERPIKIR KRITIS, BERPIKIR KREATIF, DAN KETERAMPILAN BEKERJASAMA PADA KONSEP ELEKTROPLATING - Solehudin Solehudin (Program Studi Pendidikan Kimia, FKIP, Universitas Muhammadiyah Cirebon, 2018)
This research is based on rapid technological developments, so that science and technology are one of the important foundations in nation building. Science learning is expected to deliver students to fulfill the competences in the 21st Century, to overcome low problem solving skills and to design experimental procedures and experimental device (field study, 2018). The purpose of this study was to determine the effect of STEM-based learning on understanding concepts, critical thinking skills, creative thinking, and collaborative skills on the concept of electroplating. Learning implementation applies the STEM-based approach to the Project-Based Learning (PjBL) learning model, with stages of reflection, research, discovery, application, and communication. The results showed that there was a significant effect on the posttest value of students after using STEM-based learning, with the price of ?Zcount? = 1.648 ? ?Ztable? = 0.16478. Understanding the concept of students has increased with N-gain of 0.43 which is in the medium category. The difference in the results of the pretest with posttest is significant with the price of tcount 3.62> t table 2.015. STEM-based learning influences critical thinking skills of 66.67%, creative thinking (process) 58.33%, creative thinking (product) 55.56%, collaboration skills 94.44%, and communication skills 90.48%. Keywords: PjBL STEM learning, critical thinking skills, creative thinking, collaborative skills, learning outcomes.